Religious Dimension in the Strategic Role of Disaster Mitigation Based in Bukittinggi - Juanda, Muhamad Aldi; Hanani, Silfia (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
Bukittinggi City faces significant disaster threats, particularly from earthquakes, Mount Marapi eruptions, and hydrological disasters. Disaster risk reduction mitigation activities are carried out through various schemes and programs. One such program is the Environmental Urban Resilience Program (Ketahanan Bencana Lingkungan Kelurahan or KBLK), implemented by the Bukittinggi City Disaster Management Agency (BPBD). The purpose of this research is to identify the types of activities undertaken by KBLK in disaster mitigation and to explore the roles of KBLK in disaster mitigation in Bukittinggi. A qualitative research method with a descriptive approach, utilizing observation, interviews, and documentation, was employed to understand the issues and phenomena surrounding disaster programs. This study found that five KBLK organizations in Bukittinggi conduct disaster mitigation activities, including risk assessments, disaster response planning, and contingency planning, the formation of disaster risk reduction forums (PRB), capacity building for communities in disaster management, the integration of disaster risk reduction into urban development plans, as well as activity monitoring, evaluation, and reporting. The roles and functions of disaster mitigation activities as perceived by the community include raising awareness about disasters, enhancing vigilance, and providing understanding. The functions of disaster mitigation activities felt by the community include increasing their knowledge about disaster mitigation, understanding their local conditions, and enabling them to analyze and take self-evacuation measures in the event of a disaster.